The Effect of Disciplinary Board Learning Media Based on The Problem-Based Learning on The Students' Discipline and Responsibility Character Improvement - Halimatus Sa'diyah; Syarifah Aini; Laksmi Evasufi Widi Fajari (International Journal of Education, Information Technology, and Others, 2023)
The learning process will be effective if it is aligned with the students' readiness to obey the rules and regulations of the school that reflects their discipline and responsibility characters. The learning that is designed 'by' employing the board of discipline as a medium that can provide an understanding of the discipline guidelines for school participants. This study aim was to examine the students’ improvement of discipline and responsibility characters by applying the disciplinary board media based on a problem-based learning model. The study used a quantitative method with a quasi-experiment design of pretest and posttest control group design. The study population used all students of class II which was determined by purposive sampling technique. Additionally, the technique of data analysis was descriptive statistics assisted by SPSS 26.0 using the N-Gain improvement test. The results showed that the use of the learning media of the discipline board which was based on the problem-based learning model affected the improvement of students' discipline character on average 44.7 with a correlation of 0.463 and responsibility on average 43.13 with a correlation of 0.535. The use of disciplinary board based on problem-based learning model has a positive effect on improving the character of discipline and responsibility of students simultaneously.